Building spaces & communities: the process of improving Kansas City's recycling system with community input - Heermann, Lauren (Kansas State University, 2016)
Kansas City has the opportunity to expand its recycling programs and infrastructure through a participatory design process conducted at the Kansas City Design Center (KCDC). Because participatory design techniques can allow researchers to include members of the community in the planning process, project outcomes can generally be more successful. In the example of the recycling and composting project led by students at the KCDC, an advisory committee made of professionals and members of the community represented many stakeholder interests. Because of the wide array of feedback from the community, the process of design for the studio was not linear, but rather, it transformed over a period of research, design, further research, and redesign. The students first approached local recycling issues within the scope of a document written for grant funding. However as students responded to feedback from the advisory committee, the final proposals were altered to better address truer community needs. Other aspects for how to communicate and respond to critical feedback was also realized. This report aims to discover how participatory design aided this project and made its outcomes and delivery more agreeable to the larger population.
Keywords: Community; Engagement; Co-design; Recycling; Participatory